Adoption and Impact of Kitchen Garden on Food and Nutritional Security of Farming Households in Tanzania. Issue 6 (2nd November 2022) - Sileshi, Million; Sieber, Stefan; Friedrichs, Katrin; Rybak, Constance; Feyisa, Bekele Wegi; Lana, Marcos Alberto
ABSTRACT: This article analyzes factors influencing the adoption of kitchen gardens and food and nutrition security implications of kitchen gardens on farming households. For this, the Per Capita Kilocalorie Intake (PKCI) and Food Consumption Score (FCS) were applied as food and nutrition security indicators. This paper is based on cross-sectional data that include a sample of 825 households from two districts in Tanzania. Endogenous Switching Regression is employed to determine factors influencing the adoption of a kitchen garden and its impact on food and nutrition security of the involved farming households. The results of the analysis indicate that the adoption of a kitchen garden increased with the family size (adult equivalent), credit use, access to information, districts (location), and the usage of other water sources for agriculture in addition to rainfed. It decreased with total land size and TLU. While the adoption of a kitchen garden significantly increased adopters' FCS by 1.45 or 2.96% and non-adopters' FCS by 1.26 or 2.69%. In contrast, the adoption of a kitchen garden significantly reduced non-adopters' PKCI by 101.18 or 3.92% but it does not have significant impact for adopters. Therefore, policymakers and development organizations should further promote and scale-up the kitchen garden intervention in order to use it as a tool to enhance the household's food and nutrition security.